Pengembangan Pemasaran Produk UMKM Bebasis Digital Online Tiktok dan Capcut - Izza, M; Setiawan, Drajat; Tamamudin, Tamamudin; Naja, Hilya; Ikawati, Ikawati (Jurnal Pengabdian Masyarakat, 2025)
Marketing through conventional online social media (Facebook and Whatshapp) has not been sufficient to meet the expectations desired by MSMEs, therefore it is necessary to use other social media that are more effective and potential. This empowerment method uses Active Participation Research (PAR). The number of data is 17 MSMEs in Sinbangkulon Village, Pekalongan Regency. Empowerment starts from preparation, mapping activities and live marketing actions through online media. The results of this community empowerment show that first, the majority of MSMEs already have online digital marketing media with the type of social media (Facebook and Whatshapp) with an age range of one to six years. Second, marketing through online media TikTok and CapCut is easier than on social media (58%) and this online media is used as a development marketing media (64.8% TikTok, 23.3% CapCut and other Whatshapp). Marketing on this online media has a more positive impact (64.7%) than social media (36.3%). So TikTok and CapCut have become a trend in online digital marketing development media by the majority of MSMEs as a support for product sales.